Standardisation of halal industry towards Sustainable Development Goals (SDG) - Busari, Saheed Abdullahi; Sitiris, Miszairi (IIUM Press, 2021)
The purpose of this paper is to analyse the prospects and challenges of the halal industry towards achieving health, environmental, social and economic sustainable development goal. This study relies on qualitative approach to gather data from secondary sources. The paper uses doctrinal approach to analyse the relationship between halal industry, maqāṣid sharīʿah and the sustainable development goals. The increase in demand for halal products is due to greater awareness and religious consciousness of most consumers, particularly among Muslim nations. However, there have been rising concerns about how halal industry can achieve sustainable health, environment, social and economy development goals. Even though halal industry assures halal (permissible) food by forbidding swine and alcohol businesses, it also entails an end to end ṭayyib (wholesomeness) of the products and services for a sustainable ecosystem as imbedded in maqāṣid sharīʿah. This paper explicates useful issues and challenges that principal institutions of the halal industry need to address to achieve halal sustainable development goals.